A study protocol for comparing the treatment of varicose tributaries either concomitantly with or separately from endovenous laser ablation of the incompetent saphenous trunk (the FinnTrunk Study). A multicenter parallelgroup randomized controlled study - Viljamaa Jaakko; Firoozi Khalil; Venermo Maarit; Pokela Matti; Pihlaja Toni; Halmesmäki Karoliina; Hakovirta Harri (Public Library of Science, 2026)
Background
Opinions on the treatment of varicose tributaries in relation to saphenous ablation in varicose disease vary. Moreover, the possible role of the tributaries regarding the recurrence of varicose disease remains unclear. The aim of the FinnTrunk study is to compare two different treatment strategies for varicose disease in a randomized setting. In group one, the initial treatment will entail endovenous laser ablation (EVLA) of the incompetent saphenous trunk without tributary treatment. In group two, the varicose tributaries will be treated with ultrasound-guided foam sclerotherapy (UGFS) concomitantly with truncal ablation. The primary outcome measure is the need for additional procedures during the follow-up. The secondary outcome measures are the cost of treatment and recurrence of varicose disease.
Methods
Consecutive patients with symptomatic varicose disease (CEAP clinical class C2–C3) will be screened for the study. Patients who fulfil the study criteria and give their informed consent will be scheduled for the procedure and randomized to either study group. Patients will be followed-up at 3 months, 1 year, 3 years, and 5 years. The post-procedure pain score based on a numeric rating scale (NRS) and also the use of analgesics, as well as possible procedure-related complications will be recorded at 3 months. Patient-reported outcome measures (PROMs) will be recorded at 1 year. Data pertaining to the additional treatment of varicose tributaries, the Aberdeen Varicose Vein Questionnaire (AVVQ), the Venous Clinical Severity Score (VCSS), and the health-related quality of life (EQ-5D-5L) will be collected at each follow-up visit. A duplex ultrasound (DUS) examination will be performed at each visit, and data on varicose tributaries and the need for additional treatment will be recorded.
Trial registration
Registered on ClinicalTrials.gov, ID NCT04774939.